2018
DOI: 10.1080/13691058.2018.1459846
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards same-sex parenting in Italy: the influence of traditional gender ideology

Abstract: This study aimed to examine the role of gender ideology, religiosity and political conservatism on attitudes toward same-sex parenting in Italy at a time when same-sex parent families are undergoing attacks from ideological campaigns opposing non-traditional gender roles and families. We collected data from 4,187 heterosexual respondents about attitudes towards two-father and two-mother parenting, homonegativity, attitudes toward traditional masculinity and femininity, religious involvement and political conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 37 publications
(70 reference statements)
1
23
0
Order By: Relevance
“…These findings are in line with recent studies conducted in Australia (Webb et al, 2017) and in Italy (Ioverno et al, 2019). Because of this link between traditional gender roles and negative attitudes toward same-sex parenting, it is not surprising that conservative organisations' campaigns all over the world have a good reception among right-wing oriented people with traditional beliefs about the relationship between men and women.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are in line with recent studies conducted in Australia (Webb et al, 2017) and in Italy (Ioverno et al, 2019). Because of this link between traditional gender roles and negative attitudes toward same-sex parenting, it is not surprising that conservative organisations' campaigns all over the world have a good reception among right-wing oriented people with traditional beliefs about the relationship between men and women.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have mostly focused on Fig. 1 Attitudes toward same-sex marriage and lesbian/gay parenting as a function of country attitudes toward LG people, SSM, and LGP in a single country (Costa et al, 2017;Ioverno et al, 2018;Vecho et al, 2018), 8 or two countries (Costa & Salinas-Quiroz, 2019). To our knowledge, only the European Commission study (2015) compared attitudes across different European countries.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have investigated the sociodemographic and social psychological predictors of attitudes toward homosexuality and same-sex relations, the literature on heterosexuals' attitudes toward SSM and LGP in Europe remains scarce (Costa et al, 2017;Costa & Davies, 2012;Ioverno et al, 2018). In this study, we examined heterosexual youths' attitudes toward SSM and LGP and their predictors in seven European countries.…”
mentioning
confidence: 99%
“…Despite evidence to the contrary, people often believe that same-sex couples lack parenting skills (Armesto, 2002) and that children raised by gay parents are less likely to develop normative sexual and gender identities (Carnaghi, Anderson, & Bianchi, 2018; Gato & Fontaine, 2013). Recently, Ioverno et al (2018) distinguished between (a) parenting skills , namely the practical and emotional skills to respond to the children’s needs such as their diet, hygiene, or cuddles; and (b) parental adjustment , namely the ability to provide adequate female and male role models, to face challenges, and to support the child’s development. These authors found that both dimensions are related to sexual prejudice.…”
Section: Same-sex Parenting and Adoptionmentioning
confidence: 99%